Film-Based Resources in Asynchronous Online Learning - Miftahul Furqon (Universitas Islam Negeri (UIN) Mataram, 2020)
Juxtaposed with other teaching and learning media, film-based resources in English Language teaching are succinctly beneficial to support students to learn English skills. Films facilitate students to learn English integrally, not in an isolated way. Responding to today’s trend in which the teaching and learning process is converted from offline to an online system, it is crucial to ease students to be independent learners. This paper is aimed to justify how filmbased resources can support student’s learning independence in asynchronous online learning. Specifically, the writer focuses on reviewing this issue from the Stern’s framework of teachers’ beliefs in language teaching to analyze how films can be part of the important elements in designing language teaching materials, and how asynchronous instructional method becomes a suitable decision that teachers make regarding the process of online teaching and learning. In reference to the theoretical justification, it is concluded that film-based resources conceptually facilitate student’s learning independence in asynchronous online learning. Meanwhile, regarding today’s trend in which some language teachings are converted into online learning, the asynchronous instructional method is a suitable decision that teachers can make.